The construction of substructure / Muhammad Farhan Ahmad Asri - Ahmad Asri, Muhammad Farhan (Universiti Teknologi MARA, Perak, 2013)
This report simply explained about all the process and method that involved in construction of substructure. It is made based on five month experience at site construction project. This report divided into few chapters which started with company's background and project's background. From the observation, it is clearly shows that the construction of substructure is not as easily as it seems. It included a lot time, money, labour, parties and complicated construction. In this report, it is explained about the type of pile used at the site to construct the pile foundation, the design of pile cap at site, the size of column stump and the construction of the ground beam. During the construction, few problems had occurred especially during piling work and this report has mentioned the way to solve it. As a conclusion, this report provided detail process and method for the construction of substructure.